Enhancing Entrepreneurship Awareness among Grade 10 Junior High School Students: Pathways to Livelihood Opportunities - Maroma, Adrian P. (Future Science / FSH-PH Publications, 2024)
This study assessed the level of awareness of livelihood and entrepreneurship opportunities among grade 10 junior high school students of Bulacan Province, with a view to knowing the possible entry points for educational interventions. The objectives of the research are: to find the extent to which students know available entrepreneurship opportunities and perceive the extent of entrepreneurship education in schools and the role that entrepreneurship plays in the economy. This will be a mixed-method study using both quantitative and qualitative data collection methods. It shall be participated by the Grade 10 students of two public secondary schools in Malolos, Bulacan, for the 2021-2022 academic year. Data were gathered through questionnaires adapted from the various measures, as shall be specified. The results of the study showed that the student-respondents manifested a moderate level of awareness insofar as entrepreneurship is concerned. However, some industries seemed underrepresented in the awareness that the students have about entrepreneurship. Based on the findings, promotional strategies in the form of informative posters and videos were formulated and evaluated by experts. An action plan was suggested to increase livelihood and entrepreneurship awareness, recommending activities for provoking the students' interest.